Philosophy – Ethnology – Translation on Dealing with Cultural Differences - Kaufmann, Matthias (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
There has been a long-standing connection between social anthropology and philosophy, not only because Claude Lévi-Strauss named Rousseau as the “father” of his discipline. This connection had essentially critical components insofar as the epistemological and moral premises of social anthropology were called into doubt by philosophers raising questions concerning the understanding of other cultures and their denunciation as “primitive”. On the other hand, this ongoing debate also revealed the Eurocentrism of large parts of “Western” philosophical tradition. Wittgenstein and thinkers inspired by him played an important role in revealing hidden premises and presuppositions in dealing with non-European traditions in authors such as James Frazer, but also in anthropological “classics” such as Evans-Pritchard. “Corrections” made in the anthropological discussion, which led to conceptions such as “multiple ontologies”, could have benefited from partly parallel philosophical reflections – and vice versa. Through the concept of translation, understood as the migration of objectified ideas, common elements and differences between cultures can be grasped on the basis of their integration into the various webs of belief and, among other things, the possibilities and limits of science can be evaluated in comparison to other methods of dealing with the world.